Gaya Kepemimpinan Politik Mahyeldi Ansharullah sebagai Walikota Padang Periode 2014-2019 - Felinda, Oktria; Zetra, Aidinil; Rosyidi, Bakaruddin (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This analysis of Mahyeldi Ansharullah's political leadership style as Mayor of Padang for the 2014-2019 period, departs from Mahyeldi's political leadership style as Mayor of Padang which displays a different political leadership style from the leadership of the previous Mayor. Mahyeldi had served as Deputy Mayor of the previous government period and during his leadership period, Padang City was considered to have experienced significant changes in urban development and governance as evidenced by various awards or achievements that have been obtained by Padang City. Mahyeldi, as a political leader, certainly has a certain leadership style, and there are also a number of factors that influence his political leadership. This is what is studied through research that has been conducted to find out: 1) How is the form of political leadership style applied by Mahyeldi Ansharullah as Mayor of Padang for the 2014-2019 period; 2) Factors that influence his leadership style. The theory used in this research is the theory of transformational leadership and servant leadership. This research uses descriptive qualitative research methods, selecting informants using purposive sampling and snowball sampling techniques. The result of this research is that the political leadership style applied by Mahyeldi Ansharullah as Mayor of Padang which is analysed by combining the theories of servant leadership and transformational leadership has not been fully able to be applied optimally. In this study, it was found that there are two forms of leadership style used by Mahyeldi Ansharullah; First, Mahyeldi as a regional head tries to carry out his duties and responsibilities to the community and his relationship with employees in the Padang City Government in improving performance for development and improving public services. Secondly, on the other hand in a dilemma Mahyeldi as Mayor which is a political position carried by a political party, he must accommodate political interests and must submit to the orders of his party. And the factors that influence Mahyeldi Ansharullah's political leadership style as Mayor of Padang are divided into two types, namely internal factors that come from his personality and external factors derived from the influence of his political party group.